Performance improvement of stand-alone induction generator using distribution SSC for wind power application - Mahmood T. Alkhayyat; Ziad Saeed Mohammed; Ahmed J. Ali (Institute of Advanced Engineering and Science, 2022)
Self-excited induction generators (SEIGs) are used in wind turbine system because of high reliability, rigidity, simple structure, and capability to work under severe badly operating conditions. This type of generator has a poor terminal voltage and frequency regulation during changing the connected loads due to the absence of constant excitation current. Therefore, it is essential to stabilize the generated voltage and frequency besides suppress the injected harmonic current components. In this work, the dynamic performance of SEIG with distribution static series compensator (DSSC) is analyzed. The DSSC based on neuro-fuzzy controlled (NFC) is applied to control both voltage and frequency to enhance the regulation of SEIG. The NFC is used to control the DSSC which leads to balance the requirement of the reactive and active power of stand-alone grid under load variation and attempts to obtain a constant terminal voltage. The model is simulated using MATLAB/Simulink. The NFC structure designed to regulate and control the output voltage of the SEIG driven by a wind turbine to feed a consumer in remote and rural places. Furthermore, the power system parameters calculated depending on the d-q theory. Modeling results explained that the suggested controller is consistent and tough related to the conventional types.